Kultura informacji osób z niepełnosprawnością wzroku w refleksji tyflologiczno-informatologicznej - Czerwińska, Małgorzata (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
The subject of this paper is the specificity of the information space of persons with visual disabilities as a component of their information culture, according to the concept proposed by M. Kisilowska. Based on systematic analysis of documents and long years of participative observations, the deliberations focus on legal solutions governing the access of persons with visual disabilities to information, the navigation and cognition spheres of a blind information user and the specificity of providing information, in particular the Braille system, tactile graphics, audio description, alternative materials and augmentative technologies. The deliberations highlight obstacles in accessing information by persons with visual disabilities and suggest both practical solutions and research proposals for a complex analysis of the information culture of persons with visual disabilities in Poland.